Extent of Adoption of Production and Protection Technologies of Field Pea by farmers of district Ghazipur of Uttar Pradesh (Indian Journal of Extension Education, 2011)
Field Pea (Pisum sativum L.), also called as pois proteagineux in French, guisante in Spanish, pisello in Italian, futterebse in German and matter in Hindi, is an important winter season grain legume crop largely confined to cooler temperate zone. There are two types of cultivated pea i.e. garden pea and field pea. Garden peas are harvested in an immature conditions and cooked as fresh or canned for subsequence uses. Field Pea is generally grown for dry seeds which are used for a variety of snack preparation and dal. The mature pea is highly nutritive containing high proportion of digestive protein (22.5%), carbohydrates (62.1 %), fat (1.8%), minerals (calcium, iron) and vitamins (Riboflavin, thiamine etc.). The most probable centre of origin of pea is Mediterranean region of Europe and central Asia.